1994
DOI: 10.1017/s0889189300005932
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield response of corn, soybean, and oat grown in a strip intercropping system

Abstract: Conventional Midwestern U.S. row crop agriculture has created significant environmental problems and made the farm economy reliant on government subsidies. Environmentally friendly and economically profitable alternatives are badly needed. This study addresses production characteristics of strip intercropping, a system that may meet both requirements. Two experiments were conducted in 1989 and 1990: one on a cooperating farmer's field with ridge tillage and the second at a university research farm with convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 6 publications
4
32
1
3
Order By: Relevance
“…Average yields of soybean strips MG III were 6, 13, and 11% lower than those in the monoculture, whereas in MG V yields were 2, 8, and 8% lower than those in the monocultures during C1, C2, and C3, respectively (Figure 4). Results are similar to those obtained by Pendleton et al [35], Lesoing and Francis,[20,21], West and Griffith, [15], Ghaffarzadeh et al [16], and Francis et al [27].…”
Section: Grainsupporting
confidence: 90%
See 1 more Smart Citation
“…Average yields of soybean strips MG III were 6, 13, and 11% lower than those in the monoculture, whereas in MG V yields were 2, 8, and 8% lower than those in the monocultures during C1, C2, and C3, respectively (Figure 4). Results are similar to those obtained by Pendleton et al [35], Lesoing and Francis,[20,21], West and Griffith, [15], Ghaffarzadeh et al [16], and Francis et al [27].…”
Section: Grainsupporting
confidence: 90%
“…Corn yield increased 13, 13, and 16% when cultivated with MG III soybean strip and 15, 15, and 16% with MG V soybean strip, during C1, C2, and C3, respectively (Figure 4). Results are similar to that obtained in USA [15,16], China [17], and Argentina, [18,19].…”
Section: Grain Yieldsupporting
confidence: 88%
“…Li et al (1999) noted that interspecies root interactions between intercropped fava bean and maize played an important role in increasing yield and nitrogen and phosphorus acquisition within an intercropping system. Ghaffarzadeh et al (1994) found that strip intercropping led to a 20-24% greater maize yield and a 10-15% lower soybean yield in adjacent border rows in a maize/soybean intercropping system.…”
Section: Fig 1 Maize and Bean Land Equivalent Ratio (Ler) As Affectmentioning
confidence: 95%
“…Ghaffarzadeh et al [57] observed that the potential for stress could be increased when crops compete among themselves. Ghaffarzadeh et al [58] further intimated that competition for resources might develop because of root growth patterns and/or different resource demands, although they acknowledged that there is limited information available about light, water, and nutrient competition in regard to plant position.…”
Section: Potential Versus Actual Bean Grain Yieldmentioning
confidence: 99%